External application of a Nocardia rubra cell wall skeleton in the treatment of diabetic foot ulcers - Caiqi Shen; Wuhan Wei; Aijun Zhang; Changbo Tao; Xueyang Li; Yanping Guo; Hanxiao Wei; Qiang Li; Peisheng Jin (Chinese Journal of Plastic and Reconstructive Surgery, 2022)
Diabetic foot ulcers are one of the most severe complications of diabetes that have imposed great financial and psychological burdens on diabetic patients. A Nocardia rubra cell wall skeleton (Nr-CWS) can be externally applied to accelerate wound healing. However, its clinical application has not yet been reported. Herein, we report two patients with diabetic foot ulcers treated with Nr-CWS. After wound debridement, the wound was covered with a sterile cotton ball infiltrated with an Nr-CWS that was diluted with 2.0 mL of saline. The covers were changed every two days until complete wound healing occurred. The two wounds healed after 3 and 12 weeks, respectively. This article aims to provide a new treatment for diabetic foot ulcers, with the hope that physicians may consider an Nr-CWS as a complementary method for the treatment of chronic wounds.